Studies on the biosafety of botanical insecticides to native natural enemies of mulberry ecosystem (The Journal of Plant Protection Sciences, 2020)
Laboratory studies were made to compare the toxicity of botanical insecticides viz. Neem oil, Pongamia oil and Nicotine extract in different conc./combinations along with dimethoate and dichlorvos on four coccinellid bio-control agents (Micraspis crocea, Micraspis discolor, Brumus suturalis and Scymnus bourdilloni). All botanicals tested showed least mortality and was on par with unsprayed control. Dimethoate (0.1%) was highly toxic causing 100% mortality. Whereas, dichlorvos (0.1%) was least toxic in comparison to dimethoate. Botanical insecticides tested in different  conc./combinations are compatible with natural enemies and may be incorporated in IPM in mulberry ecosystem.
Keywords: Mulberry pests; botanical insecticides; bio-safety; bio-control agents